Development of 5G Polar Experimental Kit - Anusorn Wongsa; Krittiyaporn Mueadkhunthod; Watid Phakphisut; Chatuporn Duangthong; Kidsanapong Puntsri; Thanomsak Sopon (2022 37th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2022)
The 5G polar experimental kit is presented for learning polar codes in 5G new radio. The experimental kit is developed to demonstrate the eleven encoding processes of polar codes described in 3GPP TS 38.212 technical specification. The experimental kit provides a graphical user interface (GUI) which a user can provide any the input parameters defined in the 5G new radio. The experimental kit provides a software and a hardware for a 5G polar encoder. After the polar encoder in the software or the hardware are done, the encoding results will be displayed on the GUI along with their processes details.
Keywords: Error Correcting Code Techniques; Advanced Wireless Communication Techniques; DNA and Biological Computing